Characteristics, experiences and actions taken by women to address delayed conception: A mixed-methods cross-sectional study protocol - Adhikary, Priyanka; Roy, Nivedita; Mburu, Gitau; Kabra, Rita; Habib, Ndema Abu; Kiarie, James; Dhabhai, Neeta; Chowdhury, Ranadip; Mazumder, Sarmila (PLOS ONE, 2022)
Background The impact of infertility on mental, emotional, physical and sexual health is grave, particularly in a pronatalist society. Literature is replete with evidence of wide ranging psychosocial consequences of infertility in women, indicating the need for identifying the gaps and designing appropriate context specific interventions to improve access and utilization of services. Data that are accessible, primarily from infertility clinics and women visiting hospitals for infertility treatment; information from community settings is rare. This is a protocol paper for a study to understand women’s experiences and actions taken by them to cope with delayed conception. Methods Mixed-methods cross-sectional design is used to obtain deep insights into the experiences of delayed conception, coping mechanisms, medical assistance and other help sought. Information is also being obtained on socio-demographic profile, fertility intentions, fertility quality of life, general medical history, obstetric, gynecological and sexual history, substance use and mental health status. A sample of 1530 women will be administered 4 modules of a quantitative survey. Focus group discussions, about four or till saturation point, will be conducted using purposive sampling. The study is recruiting from a population of women who previously participated in the ‘Women and Infants Integrated Interventions for Growth Study (WINGS) and failed to conceive during 18 months follow up period. Data collected through questionnaire will be assembled, cleaned, analyzed and reported. The findings will be disseminated through reports with the ethics review committee, government entities, academic and research publications. Discussion This study will provide insights on the experiences and coping strategies of women with delayed conception in the study community. Results will assist in designing appropriate interventions to meet the holistic health and psychosocial needs of women with delayed conception and promote sexual and reproductive health within the broader framework of Sustainable Development Goals and Universal health coverage. Trial registration Trial registration number: CTRI/2020/03/023955.